CONNECTIONS BETWEEN SOME MOTOR ABILITIES WITH THE RESULTS OF THE SCHOOL SUCCESS - Nazim Myrtaj; Hasim Rushiti; Abdulla Elezi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This study was conducted to determine the relationships between motor variables, variables of success from general subjects and from the subject physical education. The sample was consisted of 25 students, handball players ( in total , 75) from VIth, VIIth and VIIIth grade of the elementary school, "Selami Halači" in Gjilani, i.e. students- handball players, of age 11, 12 and 13 (± 5 months), which in addition to the regular classes of physical education had at least one year of handball practice at a school section. We used 10 tests to asses the motor skills and two tests for assessing the success of general subjects and the subject physical education (1-5). Pearson correlation matrix was used to determine the connection in the manifest space between motor variables and the variables of achievement in general subjects and the subject - physical education, at all investigated groups. The correlation results show that students, handball players aged 11 years (± 5 months) had a distinct correlation between the variables of coordination and success from the general subjects and the correlation between success in the subject of physical education and almost all motor skill's variables.